Dampak Gelombang Kapal Cepat Pada Wilayah Pesisir Pantai Yang Mengakibatkan Abrasi - Melva Noya; Ekberth Vallen Noya (Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Seacoast areas and small islands have strategic meaning in building the nation and prospering its people. This is because of the wealth of natural resources contained in this region, both biological and non-biological. However, this wealth of natural resources has not been utilized optimally, which is partly due to sectoral egos between government agencies.Purposes of the Research: To determine the impact of abrasion from the activities of fast boats with great power that cause large waves and result in an abrasion on the coast.Methods of the Research: The method used in this study is normative-juridical, which focuses on the main law by examining theories, concepts, legal principles, and laws and regulations related to this research.Results of the Research: Abrasion is the process of releasing the energy behind the waves towards the land, hitting the coastal areas, then washing away